A comparison of counselling self-efficacy among international and domestic counselling students. Issue 1 (13th June 2022) - Haktanir, Abdulkadir
Abstract: This study examined counselling self-efficacy (CSE) between international counselling students and domestic counselling students. Data were collected from 179 participants. Analysis of the data suggested similar levels of CSE scores between domestic and international counselling students, and between school counselling students and other master's-level counselling students. However, a significant difference was detected between master's- and doctoral-level counselling students in terms of their CSE scores. Implications for counsellor educators, counselling supervisors and the counselling profession are provided.